IMPLEMENTASI KEBIJAKAN PENYELENGGARAAN SMK MINI DI JAWA TIMUR - ., Hudiyono (Universitas 17 Agustus 1945 Surabaya, 2016)
Vocational High School Mini is SMK formal at boarding school who get the programcenters preparing a skilled workforce and develop the function of vocational boardingschool as a center for vocational training integrated in an effort to push the unemploymentrate is high, improving the quality of the educational process is minimal skills, andincrease the entrepreneurial spirit in self-learners. Based on this, the main problem of thisstudy are: (a) How is the implementation of policy administration SMK Mini? and (b)How does the organization of vocational Mini models in East Java?. This study used aqualitative approach and case study design. Collecting data using the technique ofparticipant observation, interview and documentation. The data were analyzed usingqualitative descriptive technique, using an interactive model of Miles and Hubermanincludes: data collection, data reduction, data presentation and verification. This studyfound: (1) the implementation of policy administration in East Java SMK Mini appliedproperly in accordance with the proportions. The process of policy implementation refersto the implementation model Edwards III. While the level of effectiveness of policyimplementation organization of vocational Mini in East Java in general demonstrateeffective, in terms of appropriate targeting and program objectives. (2) the implementationof vocational Model Mini in East Java is more taken to function as BLK (Training Center)in entrepreneurial-based boarding school; in function SMK Mini as BLK fosteringentrepreneurship skills and training of skilled labor. Entrepreneurship skills developed inthe organization of vocational Mini comprises: (a) skills of design effort in the field ofservices and production; (b) the skills to find a market; (c) skills to manage businessfinances; and (d) public relations skills. While the training of skilled labor carried out inseveral stages of a cycle of: (a) planning of the training program by identifying trainingneeds and training materials emphasize entrepreneurial skills according to market needsand based on the needs of the industrial world; (b) development of training programsthrough cooperation and training of manpower training in vocational Mini implementedwithin six months.Keywords: Policy Implementation, Vocational High School Mini